Appraisal of Technical and Economic Potential Micro Hydro Power in Bali - Suarda, Made (Jurnal Energi Dan Manufaktur, 2012)
Energy consumption particularly on electrical energy is continuously rising as a result of economical rising and community development. Therefore it needs to be responded about this condition by developing renewable energy utilization which is available. Renewable energy resources are possibly developed in Bali such as solar energy, wind energy, hydropower, sea energy, and biomass. However, one of renewable energy resources that is mostly possible to be developed in Bali is hydropower in micro scale wich is named microhydro. The microhydro works by using water flow which has debit and head. However, it needs an analysis both on technical and financial analysis. Technical analysis is carried out by checking debit and head of the water flow, and then calculates power would be generated, as well as the microhydro equipments such as a suitable choosen of turbine, generator, and control system. In other hand, financial analisis is carried out by estimating cost for construction the microhydro system, then by using Net Present Value (NPV) analysis to check that the system is profitable to be constructed. The result noted that Bali has some potential microhydros or pycohydros that are profitable to be developed both on rivers and irrigations system. Financial analyses show that microhydro systems are profitable to be constructed (NPV is positive) as long as their heads are at least 10 meters, in other side, debit are more affected their generated powers. However, in their implementations, there are some barriers in utilize those water flow resources as microhydro systems, such as those sites were used for other objects for instant as tourism destinations, or for cultures conservation, and the communities have not knew the advantages of microhydro yet therefore it needs socialization to the communities.
Keywords: Microhydro, Technical analysis, Financial analysis, Bali